La letra de cambio exigida a través del procedimiento ejecutivo y ordinario. - Guanga Chabla, Katherine Lisbeth (2018)
The present research is a critical, legal and doctrinal analysis on the bill of exchange, required through the executive and ordinary procedure, used in business areas, civil, labor, leasing and liquidation between individuals, which guarantees the collection of a debt agreed by the drawer, the subscriber (creditor) and the drawee, drawee, acceptor (debtor). This denomination is used in people's own activities and recognized and accepted by citizens. The legal basis on which this study is based, Article 347 and 348 of the General Organic Code of Processes (COGEP), which establish the obligations of giving, doing or not doing and procedures both in executive and ordinary. For this, an analysis of the executive titles that exist in the Ecuadorian legislation was carried out through practical cases and their execution, as well as, the evidence provided in the execution process for the collection of the bill of exchange, will be analyzed, in order to identify through a comparative study the executive ordinary procedures used to collection of a bill of exchange in the Ecuadorian legislation. As a result, the legislation will be used, as a doctrine that will allow deciphering, if the procedures for the execution of collection of the bill of exchange established in the General Organic Code of Processes are effective.